SIMULTANEOUS DETERMINATION OF PHYTOCHEMICALS IN RHYNCHOSIA CAPITATA BY RP-HPLC AND GC/MS; ITS ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY - R.PRAVEENA; V.DEEPHA; K.SADASIVAM (International Journal of Pharma and Bio Sciences, 2013)
The search for novel drugs from higher plants led to the analysis of a novel plant source Rhynchosia capitata for its phytoconstituents. GC/MS study confirm the presence of oleic acid, octadecanoic acid, phytol, hexadecanoic acid, E-11-hexadecenoic acid, Z,Z,Z-4,6,9-nonadecatriene, tetradecanoic acid, 5-azulenemethanol and1-butanol. A highly sensitive reverse phase high performance liquid chromatographic analysis is carried out to detect the presence of five plant phenolics namely gallic acid, caffeic acid, ferulic acid, rutin and quercetin. Antioxidant activity is tested via DPPH assay and antimicrobial activity for the human pathogenic strains Staphylococcus aureus, Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa is also carried out. A comparison of the antioxidant and antimicrobial activity of the ethanol extract revealed antioxidant behavior to be dominant.